2019
DOI: 10.5488/cmp.22.43606
|View full text |Cite
|
Sign up to set email alerts
|

X-rays induced atomic dynamics in a lithium-borate glass

Abstract: The continuous development of synchrotron-based experimental techniques in the X-ray range provides new possibilities to probe the structure and the dynamics of bulk materials down to inter-atomic distances. However, the interaction of intense X-ray beams with matter can also induce changes in the structure and dynamics of materials. A reversible and non-destructive beam induced dynamics has recently been observed in X-ray photon correlation spectroscopy experiments in some oxide glasses at sufficiently low ab… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 20 publications
(42 reference statements)
1
8
0
Order By: Relevance
“…4(a)]. This result confirms previous studies of the x-ray beam induced dynamics in oxide glasses [9][10][11][12]. The corresponding values averaged over the curves measured with different x-ray dose rates are reported in Fig.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…4(a)]. This result confirms previous studies of the x-ray beam induced dynamics in oxide glasses [9][10][11][12]. The corresponding values averaged over the curves measured with different x-ray dose rates are reported in Fig.…”
Section: Resultssupporting
confidence: 89%
“…[10] for a boron oxide glass, in Ref. [12] for a lithium borate glass, and in Ref. [11] for a series of Rb and Cs borate glasses; a compressed exponential decay (β > 1) has instead been observed in Ref.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Recent investigations of microscopic dynamics in oxide glasses by XPCS revealed faster than expected relaxation times in a deep glassy state related to the beam-induced effect (Ruta et al, 2017;Dallari et al, 2019;Pintori et al, 2019;Holzweber et al, 2019). In all of the above cases (Ruta et al, 2017;Dallari et al, 2019;Pintori et al, 2019;Holzweber et al, 2019) the X-ray probe interacts with the sample and causes artificial structural relaxations that otherwise should not occur in the sample.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations of microscopic dynamics in oxide glasses by XPCS revealed faster than expected relaxation times in a deep glassy state related to the beam-induced effect (Ruta et al, 2017;Dallari et al, 2019;Pintori et al, 2019;Holzweber et al, 2019). In all of the above cases (Ruta et al, 2017;Dallari et al, 2019;Pintori et al, 2019;Holzweber et al, 2019) the X-ray probe interacts with the sample and causes artificial structural relaxations that otherwise should not occur in the sample. It was clearly identified that the measured relaxation times scale inversely with the intensity of the X-ray beam (Ruta et al, 2017;Pintori et al, 2019;Holzweber et al, 2019) and that the sample dynamics and beam-induced dynamics are independent processes (Pintori et al, 2019).…”
Section: Introductionmentioning
confidence: 99%